Clastic rock geochemistry of the Sirohi Basin, Aravalli Craton, NW India: Implications for paleoweathering, provenance and geodynamics - Tavheed Khan; D. Srinivasa Sarma (Geosystems and Geoenvironment, 2023)
Sirohi Basin of Trans-Aravalli Region, Rajasthan preserves a thick clastic sequence composed of phyllite and metasandstone. Based on their petrochemical properties, metasandstone is classified as K-feldspar rich wacke (Wacke I) and plagioclase rich wacke (Wacke II). Wacke I is characterised by higher K2O, Fe2O3 and lower CaO, Na2O, and Na2O/K2O ratios than Wacke II. Chemical Index of Alteration (CIA) and the A-CN-K systematic prescribe least chemical weathering for the sediments of Wacke II, moderate for Wacke I and moderately intense for phyllite of the Sirohi Basin. Chemical traits perceived from UCC spidergrams, discrimination function diagrams, etc. in conjunction with immobile element ratios (e.g., Al2O3/TiO2, Th/Sc, La/Sc, La/Co, Th/Co, Eu/Eu*, La/SmN and Gd/YbN) establish dual-source terrains for Sirohi clastics, one with preponderance of felsic componets and other mafic plus felsic ingrediatns. The petrochemical signatures of Sirohi clastics, though suggest procurement of detritus form diffrent sources but consanguineous evolution in the Sirohi Basin, in response to extensional stresses.